Continuous control of classical-quantum crossover by external high pressure in the coupled chain compound CsCuCl3 - Daisuke Yamamoto (Nature Portfolio, 2021)
In real materials, a spin quantum number assumes a fixed value, which makes it challenging to realize a crossover between quantum and classical spin regimes. Here the authors demonstrate such a crossover in a weakly coupled chain compound by controlling the amount of quantum correlations, in the form of the inverse spin quantum number, with external pressure.